(untitled) (Advances in Applied Mathematics and Mechanics, 2020)
In this paper, we solve linear parabolic integral differential equations using the weak Galerkin finite element method (WG) by adding a stabilizer. The semi-discrete and fully-discrete weak Galerkin finite element schemes are constructed. Optimal convergent orders of the solution of the WG in L^2 and H^1 norm are derived. Several computational results confirm the correctness and efficiency of the method.